Manajemen dan Kualitas Pendidikan di Eta Otonomi Pendidikan - Imam Syafi'ie (Millah: Journal of Religious Studies, 2001)
The Act No. 221999 on regional government and No. 251999 on the balance of finance between central government and regional government, have vast impact on all aspects of the nation life. The impacts are not only on politic and economic aspects, but they also have logic consequence on the changes of Indonesian education form and system. Based on the rules above, the education process in schools should be independent gradually and will not depend on central government moreover on regional government especially in finance. Consequenly, the quality of school must be improved either in planning or process or outcome aspect. To reach the aimed quality of the schools need a management system that can improve the quality of schools. In this frame, this writing offers the total quality management system as a medium to autonomous education having a certain quality in decentralization era.